2021
DOI: 10.1177/11206721211066705
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for corneal epithelial wound healing: Can sex play a role?

Abstract: Purpose To determine if sex is associated with corneal epithelial wound healing time in patients with persistent corneal epithelial defects (PCEDs). Methods Retrospective case series on patients with PCED from November 2014 to January 2019. Records of 127 patients with diagnosis of PCED were reviewed. Patients with an epithelial defect that lasted more than two weeks in the absence of an active corneal infection were included. Main outcome was corneal epithelial wound healing time. Results 55 patients (29 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Although no sex differences were observed associated with the epithelial defects in our study, a retrospective study showed that women of the same age, with the same risk factors and treatment plans, healed significantly more slowly than men. 132 , 133 A literature review reported that sex is not a risk factor for epithelial defects in dogs. 134 This finding suggests that there may be species-specific differences in corneal healing, and more studies are needed to delineate the effect of sex on corneal epithelial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Although no sex differences were observed associated with the epithelial defects in our study, a retrospective study showed that women of the same age, with the same risk factors and treatment plans, healed significantly more slowly than men. 132 , 133 A literature review reported that sex is not a risk factor for epithelial defects in dogs. 134 This finding suggests that there may be species-specific differences in corneal healing, and more studies are needed to delineate the effect of sex on corneal epithelial defects.…”
Section: Discussionmentioning
confidence: 99%
“…In general, all corneal layers may be affected by morphological and functional changes in diabetic eyes, and a variety of alterations have been described [81]. Indeed, the metabolic stress induced by chronic hyperglycemia activates several pathological pathways, resulting in endothelium damage, corneal edema, endothelial cells loss, progressive deprivation in corneal nerve fiber mass with consequent increased epithelial fragility, reduced epithelial cell density and corneal susceptibility to persistent epithelial defects, recurrent corneal ulcerations and infections [82][83][84]. In addition, due to the inability of the corneal endothe-lium to regenerate in response to the endothelial cell loss, compensatory morphological changes of the endothelial cells can be observed, such as increased cellular pleomorphism, polymegathism and decrease in the percentage of hexagonal cells (Hex) [83].…”
Section: Corneal Biomarkersmentioning
confidence: 99%